Pengaruh Tingkat Pemahaman Sertifikasi Chartered Accountant (CA), Motivasi Karir dan Prestasi Akademik Terhadap Minat Mahasiswa Untuk Mengambil Sertifikasi Profesional CA Pada Mahasiswa Program Studi Akuntansi Uviversitas Hindu Indonesia - Gusti Ayu Bintang Apriliani; I Wayan Sudiana; Ni Putu Ayu Kusumawati (Hita Akuntansi dan Keuangan, 2026)
For accounting graduates hoping to work in the sector, particularly as professional accountants, the Chartered Accountant (CA) credential is crucial. The participants in this study were students from the Accounting Study Program at the Faculty of Economics, Business, and Tourism, and there were a total of 222 responses. This research used a numbers-based approach. The data analysis included methods like multiple linear regression, determining coefficients, F-tests, and t-tests. The results show that students’ desire to earn a professional certification as chartered accountants is positively and strongly influenced by how much they know about CAs. Additionally, students' interest in getting the CA certificate is also greatly affected by their career ambitions. Their motivation to pursue CA certification is notably influenced by how well they perform in their studies.